Comparative Measurements of Greek Lignite Ash and Disposal Materials - Kaissas, Ioannis; Skoumbris, K. (HNPS Advances in Nuclear Physics, 2025)
Coal power plants produce big volumes of ash via the combustion procedure. Most of the fly ash is detained with appropriate filters and the bottom ash gathers at the lower levels of the combustion chamber. Large volumes of ash are disposed to refill the old coal mines, and a small part is exploited in the cement production industry. The refilling material mostly contains fly ash and material which consists of soil and negligible amounts of coal and therefore not useful for power production. This study compares the concentrations of radionuclides in fly ash samples before and after the deposition as a refilling material. The method of measurement involves preparation of the sample and γ spectroscopy with High Purity Germanium detector. Higher concentrations in pure ash appeared for the radionuclides 226Ra and 40K, 318 Bq/kg and 382 Bq/kg, respectively. In addition, comparison among the different regions of ash deposition is conducted. Even samples from the same area differ in radionuclides’ concentration. The results are in line with older studies, ordered by Public Power Corporation, and reveal that the concentrations are close to or below the clearance levels, set by the Euratom directive of 2013.